FIGURATIVE LANGUAGE IN SIMPLE PLAN’S ALBUM NO PADS, NO HELMETS … JUST A BALLS: SEMANTICS AND SEMIOTICS STUDY - Rendo, Antonius; Hendar (SAMPURASUN, 2025)
This article purposed to conduct a comprehensive analysis of figurative language found in the lyrics of Simple Plan's album "No Pads, No Helmets... Just Balls," as well as to explore its semiotic implications. The background of this research is rooted in the recognition that popular music lyrics are not only artistic expressions but also complex linguistic constructions that reflect broader cultural and emotional narratives. Despite the widespread influence of popular music, systematic studies combining figurative language analysis with semiotic interpretation remain limited, particularly in contemporary pop-punk genres. The research employs a qualitative descriptive method, focusing on an in-depth examination of five selected songs from the album. The analysis is grounded in Leech's (1981) theory of figurative language, which categorizes various forms of figurative expressions, and Barthes' (1977) theory of semiotics, which delves into the relationship between signs and meanings. The findings of this study reveal that the lyrics utilize five distinct types of figurative language: metaphor, personification, hyperbole, simile, and alliteration. Each of these elements plays a crucial role in enhancing the lyrical content, contributing to the overall impact of the songs. This research underscores the idea that figurative language serves not only as a tool for variation in expression but also as a powerful means to convey complex emotions and to establish a specific atmosphere within the music. Furthermore, the semiotic analysis indicates that the lyrics predominantly convey connotative meanings, which add layers of significance for the reader or listener. These connotations enrich the understanding of the songs, allowing for a deeper emotional connection and interpretation. By examining the interplay between figurative language and semiotics, this study contributes scientifically to the fields of linguistics, literary studies, and cultural semiotics. It expands understanding of how linguistic creativity in music can shape emotional resonance and cultural meaning, offering new perspectives on the analysis of language in popular media. In addition, the interplay between figurative language and semiotics contributes to a greater appreciation of how Simple Plan's lyrics resonate with audiences, highlighting the intricate ways in which language can evoke feelings and create meaning in the context of popular music. Keywords: figurative language, lyric analysis, popular music, simple plan, semiotics